Pengaruh Iklim Organisasi Sekolah Terhadap Motivasi Kerja Guru SD di Kecamatan Kaliwungu Kabupaten Kudus - Munziati Munziati; Sri Utaminingsih; Rismiyanto Rismiyanto (STABN RADEN WIJAYA WONOGIRI, 2023)
The research objective was to analyze the effect of organizational climate on the work motivation of elementary school teachers in the Kaliwungu sub-district, Kudus Regency. This type of research is quantitative. The research approach used in this study used ex post facto research. The population of this study were all elementary school teachers in Kaliwungu District, Kudus Regency, totaling 240 teachers. The research sample was 150 teachers using a proportional random sampling technique. The research instrument was a questionnaire. Data analysis consisted of validity test, reliability test, normality test, linearity test and linear regression test. The results showed that there was an effect of school organizational climate on teacher work motivation in the Kaliwungu sub-district, Kudus Regency with the regression equation Y = 48.937 + 0.362X